Influence of Temperature-Guided SAM Growth on Wetting and Its Mass Transfer Models - Chowdhury P.; Jha A.; Bhandary D. (My University, 2025)
The formation and growth of self-assembled monolayers (SAMs) composed of amphiphiles have garnered significant attention due to their diverse technical applications. This article reports the findings of molecular dynamics simulations aimed at elucidating the intricate relationship between the wetting behavior of amphiphiles, specifically n-alkanols, and the growth of their SAMs on a mica surface under varying temperature conditions. The investigation quantifies the structural characteristics of the formed SAMs, including density profiles, in-plane radial distribution functions, order parameters, and end-to-end length distributions of n-alkanol molecules within the SAM. Thermodynamic properties, such as the second virial coefficient and excess entropy, are examined in relation to temperature and time. The growth of the SAM is assessed by analyzing characteristic time scales at different temperatures and in-plane diffusion of n-alkanol molecules and utilizing classical theories of mass transfer to quantify the growth rate as a function of temperature. These results are then correlated with changes in the contact angle and spreading coefficient of n-alkanol droplets on the mica surface over time, providing insights into the impact of SAM growth on the wetting behavior and the mass transfer model of such systems. © 2023 American Chemical Society.